# prove thattanA + 2tan2A + 4tan4A + 8cot8A = cotA

420 Points
13 years ago

Solving from right
tan A + 2tan2A + 4tan4A + 8cot8A = tan A + 2tan2A + 4tan4A + 8/tan8A
= tan A + 2tan2A + 4tan4A + 8(1-tan24A)/2tan4A
= tan A + 2tan2A + [{4tan4A(tan4A)} + 4 (1-tan24A)]/tan4A
= tan A + 2tan2A + [4tan24A + 4 - tan24A]/tan4A
= tan A + 2tan2A + 4/tan4A

Proceeding as above, we will reach to
tan A + 2tan2A + 4tan4A + 8cot8A = 1/tanA = cotA
Hence proved.

All the best.

AKASH GOYAL

Please feel free to post as many doubts on our discussion forum as you can. We are all IITians and here to help you in your IIT JEE preparation.

Win exciting gifts by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.

509 Points
13 years ago

TANA + 2TAN2A + 4TAN4A + 8COT8A = COTA .........1

WE HAVE FORMULA , COTA-TANA=2COT2A

EQ 1 CAN BE WRITTEN AS

2TAN2A + 4TAN4A + 8COT8A = COTA-TANA

2TAN2A + 4TAN4A + 8COT8A = 2COT2A               ( BY USING FORMULA )

4TAN4A + 8COT8A = 2COT2A - 2TAN2A

4TAN4A + 8COT8A =4COT4A                               (BY USING FORMULA)

8COT8A = 4COT4A - 4TAN4A

=8COT8A                        (BY USING FORMULA )

HENCE PROVED

Rishi Sharma
3 years ago
Dear Student,

Solving from right
tan A + 2tan2A + 4tan4A + 8cot8A
= tan A + 2tan2A + 4tan4A+ 8/tan8A
= tan A + 2tan2A + 4tan4A + 8(1-tan24A)/2tan4A
= tan A + 2tan2A + [{4tan4A(tan4A)} + 4 (1-tan24A)]/tan4A
= tan A + 2tan2A + [4tan24A + 4 - tan24A]/tan4A
= tan A + 2tan2A + 4/tan4A
Proceeding as above, we will reach to
tan A + 2tan2A + 4tan4A + 8cot8A = 1/tanA = cotA

Thanks and Regards